Cabinet Decree No. 32 of the year 2024 Amending Certain Provisions of the Executive Regulations of the Mortgage Finance Law Promulgated By Prime Minister Decree No. 1 for the Year 2001 = قرار مجلس الوزراء رقم 32 لسنة 2024 بتعديل بعض أحكام اللائحة التنفيذية لقانون التمويل العقاري الصادرة بقرار مجلس الوزراء رقم 1 لسنة 2001 - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic